Surgical management of bilateral congenital coloboma of the iris and congenital cataract - N.F. Bobrova; D.V. Smaglii (Ukrainian Society of Ophthalmologists, 2018)
Background. A combined character of a defect, which is congenital coloboma in the presence of congenital cataract, brings up an issue of choosing optimal management to achieve the maximum possible optical functions, provided that the risk of development of operational and postoperative complications is reduced. Purpose. To analyze a character, features, and complications and to develop the optimal surgical management of bilateral congenital iris coloboma and cataract. Material and Methods. Visual acuity testing, standard ophthalmic examination, distance ultrasound biometry, keratometry, ultrasound scanning were performed. Results and Conclusions. We performed minimally invasive surgery including phacoemulsification of congenital cataract with IOL endocapsule implantation and formation of optic diaphragm without interventions in the iris. Visual acuity in the pseudophakic left eye increased to 1.0 within 3 months, additional diaphragming was not able to correct visual acuity. High visual acuity, 1.0, remained in the right eye in the presence of coloboma of the iris and partial cataract. Binocular vision was achieved. The autoplasty method using the proper lens capsule for coloboma of the iris made it possible to maximally improve visual acuity in the eyes with double congenital abnormality of the iris and the lens. The reasonable attitude to corepraxy, considering the bilateral damage, enabled to achieve binocular vision within the shortest possible period of time after surgery.